2016
DOI: 10.1038/srep19631
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol varies with season and lifestyle and relates to human interactions in German shepherd dogs

Abstract: It is challenging to measure long-term endocrine stress responses in animals. We investigated whether cortisol extracted from dog hair reflected the levels of activity and stress long-term, during weeks and months. Hair samples from in total 59 German shepherds were analysed. Samples for measuring cortisol concentrations were collected at three occasions and we complemented the data with individual scores from the Canine Behavioural Assessment and Research Questionnaire (C-BARQ). Generalised linear mixed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 32 publications
3
52
3
Order By: Relevance
“…Competition dogs had higher hair cortisol concentrations than both companion and working dogs and this was especially obvious in January (Roth et al 2016). Cortisol increases could possibly be related to variations in the number of training days, as competing dogs usually train less during the winter and more during the spring, in accordance with the competition season.…”
Section: Lifestyle Of the Dogmentioning
confidence: 93%
See 3 more Smart Citations
“…Competition dogs had higher hair cortisol concentrations than both companion and working dogs and this was especially obvious in January (Roth et al 2016). Cortisol increases could possibly be related to variations in the number of training days, as competing dogs usually train less during the winter and more during the spring, in accordance with the competition season.…”
Section: Lifestyle Of the Dogmentioning
confidence: 93%
“…It had been assumed that the amount of cortisol in a dog's coat increases with increasing age, but the research has not confirmed this hypothesis (Bennet and Hayssen 2010; Svendsen and Sondergaard 2014;Roth et al 2016). No correlation between HCC and age was found in grizzly bears (Macbeth et al 2010), polar bears (Bechshoft et al 2011) or humans (Kirschbaum et al 2009).…”
Section: Dog Agementioning
confidence: 93%
See 2 more Smart Citations
“…As can be seen from the results of this study, the cortisol concentration in Busha cows and heifers was significantly lower in the distal part of the hair, in comparison to proximal part. Since it was reported that solar (UV) radiation destroys cortisol (23,24), we believe that this also happened with the cortisol in hair of Busha cattle. These were kept outside and exposed to varied weather conditions which might have resulted in gradual cortisol degradation in the hair.…”
Section: Discussionmentioning
confidence: 99%